Echocardiographic assessment of pulmonary arterial stiffness in human immunodeficiency virus‐infected patients. Issue 6 (30th April 2019) - Cerik, Idris Bugra; Meric, Murat; Gulel, Okan; Ozturk Cerik, Hatun; Coksevim, Metin; Soylu, Korhan; Deveci, Aydin; Sahin, Mahmut
Abstract: Background: Pulmonary hypertension (PH) is one of the complications of human immunodeficiency virus (HIV) infection. Despite the emergence of effective therapies, pulmonary arterial hypertension is commonly seen, especially at advanced stages. At the time of diagnosis, a majority of patients are at New York Heart Association‐Functional Class III or IV. Many of the current screening modalities are dependent on detecting a rise in pulmonary arterial pressure (PAP). However, high capacitance of the pulmonary circulation implies that early microcirculation loss is not accompanied by a change in resting PAP. Therefore, we aimed to demonstrate early changes in pulmonary vascular disease in HIV‐infected patients with a new echocardiographic parameter, called as pulmonary arterial stiffness (PAS). Methods and Results: Thirty‐six HIV‐infected patients and 36 age‐ and sex‐matched healthy control subjects were enrolled in this study. PAS was calculated echocardiographically by using maximal frequency shift and acceleration time of the pulmonary artery flow trace. There was no significant difference in diastolic functions, right ventricular diameters, systolic PAP, inferior vena cava widths, right atrial area, and tricuspid annular plane systolic excursion values between the two groups. However, PAS was calculated as 24.3 ± 6.4  Hz/msn in HIV‐infected patients and 19.3 ± 3.1  Hz/msn in healthy control group ( P  < 0.001). Increase in PAS was correlated with duration of HIV infection ( P  < 0.05). Conclusion: Our results suggest that HIV infection affects pulmonary vascular bed starting early onset of disease and this can be demonstrated by an easy‐to‐measure echocardiographic parameter.